FRI0242 Association between clinical and radiographic responses, and physical function in a phase 3 study of sarilumab plus methotrexate in patients with active, moderate-to-severe rheumatoid arthritis. (15th June 2017) - Genovese, MC; Hoogstraten, H van; Kampman, W; Jayawardena, S; Huizinga, TW
Abstract : Background: In MOBILITY (NCT01061736 ), SC sarilumab (150 or 200 mg q2w) + MTX demonstrated efficacy in adults with RA and inadequate response to MTX. The most common TEAEs were infections, neutropenia, injection site reactions, and increased transaminases. Objectives: To examine association between clinical response and radiographic progression and functional response (HAQ-DI) in MOBILITY. Methods: In this post hoc analysis, associations between HAQ-DI and clinical efficacy categories (CDAI, DAS28-CRP, SDAI, and Boolean-based ACR/EULAR remission) were tested at wk 16. Trend for change from baseline (BL) in HAQ-DI across response categories was assessed using the Jonckheere-Terpstra test. Results: Regardless of definition, percentage achieving remission (CDAI ≤2.8, DAS28-CRP <2.6, SDAI ≤3.3) or no x-ray progression was higher with sarilumab vs Pbo ( P <0.05). Overall, there was a significant trend between magnitude of clinical response at wk 16 and improvement in physical function (Table). This trend was also observed for radiographic progression (mTSS change from BL), regardless of cutoff (≤0.5 and ≤0). In patients achieving remission, there was a numerically greater improvement in HAQ-DI with sarilumab vs placebo (Pbo). Even if patients did not achieve remission or LDA, the sarilumab group had generally greater numerical improvements in HAQ-DI vs Pbo. Conclusions: Achieving LDA or remission, or absence of radiographic progression, was associated with overall greater improvement in physical function. Irrespective of whether patients achieved remission or LDA, sarilumab + MTX showed greater improvements in HAQ-DI than Pbo + MTX. Acknowledgements: This study was sponsored by Sanofi Genzyme and Regeneron Pharmaceuticals, Inc. Editorial support was provided by MedThink SciCom and funded by Sanofi Genzyme and Regeneron Pharmaceuticals, Inc. Disclosure of Interest: M. Genovese Grant/research support from: Roche, Sanofi, GlaxoSmithKline, R-Pharma, RuiYi, and Bristol-Myers Squibb, Consultant for: Roche, Sanofi, GlaxoSmithKline, R-Pharma, RuiYi, and Bristol-Myers Squibb, H. van Hoogstraten Shareholder of: Sanofi Genzyme, Employee of: Sanofi Genzyme, W. Kampman Shareholder of: Regeneron Pharmaceuticals, Inc, Employee of: Regeneron Pharmaceuticals, Inc, S. Jayawardena Shareholder of: Sanofi Genzyme, Employee of: Sanofi Genzyme, T. Huizinga Consultant for: Sanofi, Roche, and Abblynx.